Sibilant production in Hebrew-speaking adults: Apical versus laminal. (4th March 2018) - Icht, Michal; Ben-David, Boaz M.
ABSTRACT: The Hebrew IPA charts describe the sibilants /s, z/ as 'alveolar fricatives', where the place of articulation on the palate is the alveolar ridge. The point of constriction on the tongue is not defined – apical (tip) or laminal (blade). Usually, speech and language pathologists (SLPs) use the apical placement in Hebrew articulation therapy. Some researchers and SLPs suggested that acceptable /s, z/ could be also produced with the laminal placement (i.e. the tip of the tongue approximating the lower incisors). The present study focused at the clinical level, attempting to determine the prevalence of these alternative points of constriction on the tongue for /s/ and /z/ in three different samples of Hebrew-speaking young adults (total n = 242), with typical articulation. Around 60% of the participants reported using the laminal position, regardless of several speaker-related variables (e.g. tongue-thrust swallowing, gender). Laminal production was more common in /s/ (than /z/), coda (than onset) position of the sibilant, mono- (than di-) syllabic words, and with non-alveolar (than alveolar) adjacent consonants. Experiment 3 revealed no acoustical differences between apical and laminal productions of /s/ and of /z/. From a clinical perspective, we wish to raise the awareness of SLPs to the prevalence of the two placements when treating Hebrew speakers, noting that tongue placements were highly correlated across sibilants. Finally, we recommend adopting a client-centred practice, where tongue placement is matched to the client. We further recommend selecting targets for intervention based on our findings, and separating between different prosodic positions in treatment.